First Grade Teachers’ Expectations of Children’s Skills in Transition to Primary School - Lara Fridani (Indonesian Journal of Economics, Social, and Humanities, 2020)
This study investigated first grade primary school teachers’ expectations of children’s skills entering primary school in Jakarta, the capital city of Indonesia. The aim of the study was to provide some reasons or beliefs that form teachers’ expectations regarding children’s competency and learning in their first year of primary school. The study was conducted using a qualitative approach which involved 30 first grade primary school teachers across Jakarta’s regions (Centre, East, West, South, and North). The Focus Group Discussion was used as an instrument that provides a forum for teachers to describe their expectations. The study employed the Ritchie and Spencer’s qualitative analysis framework analysis approach (1994) which involved five key stages: familiarization, identifying a thematic framework, indexing, charting and mapping, and interpretation. The results showed that expected academic skills, teachers’ competency, and educational policy were the key variables that informed teachers’ expectations. The findings of this study have demonstrated that it is crucial to support teachers professional development as their knowledge and expectation may greatly affect the way teachers treat their students.